Zadania samorządów gminnych województwa lubelskiego w zakresie ochrony zdrowia = The tasks of local governments Lublin province about Healthcare - Warchoł, Martyna; Furtak-Niczyporuk, Marzena (Journal of Education, Health and Sport, 2016)
Warchoł Martyna, Furtak-Niczyporuk Marzena. Zadania samorządów gminnych województwa lubelskiego w zakresie ochrony zdrowia = The tasks of local governments Lublin province about Healthcare. Journal of Education, Health and Sport. 2016;6(7):218-227. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57348 http://ojs.ukw.edu.pl/index.php/johs/article/view/3688 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 09.07.2016. Zadania samorządów gminnych województwa lubelskiego w zakresie ochrony zdrowia The tasks of local governments Lublin province about Healthcare Martyna Warchoł1, Marzena Furtak-Niczyporuk2 1absolwent Uniwersytetu Medycznego w Lublinie 2Katedra i Zakład Zdrowia Publicznego, Uniwersytet Medyczny w Lublinie Adres do korespondencji dr n. med. Marzena Furtak-Niczyporuk Uniwersytet Medyczny w Lublinie 20 – 081 Lublin ul. Chodźki 1 Abstrakt Wprowadzenie Gmina jest podstawową jednostką samorządu terytorialnego. Konstytucja RP określa gminę jako podstawową jednostkę samorządu terytorialnego. Dostęp do świadczeń opieki zdrowotnej gwarantuje obywatelom art. 68 ust 1 Konstytucji RP. W ust. 2 tegoż artykułu nakłada na władze publiczne obowiązek zapewnienia równego dostępu do opieki zdrowotnej finansowanych ze środków publicznych. Zgodnie z u. s. g. do zadań własnych gminy należy zaspokajanie potrzeb zbiorowych wspólnoty w sprawach ochrony zdrowia. Cel pracy Celem pracy jest przedstawienie działalności samorządu gminy w zakresie ochrony zdrowia na terenie województwa lubelskiego. Materiał i metody W badaniu zastosowano metodę sondażu diagnostycznego. Narzędziem badawczym był kwestionariusz ankiety własnego autorstwa złożony z 24 pytań. Grupę badaną stanowili urzędnicy 213 samorządów gminnych województwa lubelskiego, z czego 170 to gminy wiejskie, 23 to gminy miejsko – wiejskie, 20 to gminy miejskie. Badania odbywały się na zasadzie anonimowości. Ankiety zostały wysyłane do respondentów za pomocą Internetu. Wyniki i wnioski Z badań wynika, że jednostki samorządu terytorialnego podejmują bardzo okrojone działania w zakresie ochrony. Często nie wykonując obowiązkowych zadań do których zobowiązują ich normy prawne. Słowa kluczowe: gmina, ochrona zdrowia, zadania. Abstract Introduction The municipality is the basic unit of local government. The Constitution defines the municipality as the basic unit of local government. Access Health Care Services do guarantee citizens the art. 68 of the Constitution Paragraph 1. Paragraph. 2 of the same article imposes on the public authorities to ensure equal access to health care financed from public funds. According to the u. S. Sol. do commune’s own tasks must satisfy the collective needs of the community in matters of Health. Aim The aim of the study is to present the activities of local Municipality in the field of Health in the province of Lublin. Material and Methods The study used a method of diagnostic survey. The research tool was a questionnaire Polls own authorship consisting of 24 questions. The study group comprised 213 officials of local governments of Lublin province, of which 170 Rural Municipalities, 23 Municipalities to urban - Rural, 20 Municipalities. Research conducted on the principle of anonymity. Surveys were sent to do the respondents using the Internet. The results and conclusions The research shows that local governments take very truncated activities Protection. Often without the mandatory tasks for which oblige them legal standards. Keywords: community, healthcare, tasks, local governments.